Early and ongoing stable glycaemic control is associated with a reduction in major adverse cardiovascular events in people with type 2 diabetes: A primary care cohort study. Issue 7 (18th April 2022) - Whyte, Martin B.; Joy, Mark; Hinton, William; McGovern, Andrew; Hoang, Uy; van Vlymen, Jeremy; Ferreira, Filipa; Mount, Julie; Munro, Neil; de Lusignan, Simon
Abstract: Aim: To determine whether achieving early glycaemic control, and any subsequent glycaemic variability, was associated with any change in the risk of major adverse cardiovascular events (MACE). Materials and Methods: A retrospective cohort analysis from the Oxford‐Royal College of General Practitioners Research and Surveillance Centre database—a large, English primary care network—was conducted. We followed newly diagnosed patients with type 2 diabetes, on or after 1 January 2005, aged 25 years or older at diagnosis, with HbA1c measurements at both diagnosis and after 1 year, plus five or more measurements of HbA1c thereafter. Three glycaemic bands were created: groups A (HbA1c < 58 mmol/mol [<7.5%]), B (HbA1c ≥ 58 to 75 mmol/mol [7.5%‐9.0%]) and C (HbA1c ≥ 75 mmol/mol [≥9.0%]). Movement between bands was determined from diagnosis to 1 year. Additionally, for data after the first 12 months, a glycaemic variability score was calculated from the number of successive HbA1c readings differing by 0.5% or higher (≥5.5 mmol/mol). Risk of MACE from 1 year postdiagnosis was assessed using time‐varying Cox proportional hazards models, which included the first‐year transition and the glycaemic variability score. Results: From 26 180 patients, there were 2300 MACE. Compared with group A‐>A transition over 1 year, those with C‐>A transition had a reduced risk of MACE (HR 0.75; 95% CI 0.60‐0.94; P  = .014), whereas group C‐>C had HR 1.21 (0.81‐1.81; P  = .34). Compared with the lowest glycaemic variability score, the greatest variability increased the risk of MACE (HR 1.51; 1.11‐2.06; P  = .0096). Conclusion: Early control of HbA1c improved cardiovascular outcomes in type 2 diabetes, although subsequent glycaemic variability had a negative effect on an individual's risk.